Serum matrix metalloproteinase-9 (MMP-9) as a biomarker in paediatric and adult tick-borne encephalitis patients - Fortova, Andrea; Hönig, Vaclav; Salat, Jiri; Palus, Martin; Pychova, Martina; Krbkova, Lenka; Barkhash, Andrey V; Kriha, Michal F; Chrdle, Ales; Lipoldova, Marie; Ruzek, Daniel (Virus research, 2023)
Matrix metalloproteinases (MMPs) play an important role in central nervous system infections. We analysed the levels of 8 different MMPs in the cerebrospinal fluid (CSF) of 89 adult patients infected with tick-borne encephalitis (TBE) virus and compared them with the levels in a control group. MMP-9 was the only MMP that showed significantly increased CSF levels in TBE patients. Serum MMP-9 levels were subsequently measured in 101 adult TBE patients at various time points during the neurological phase of TBE and at follow-up. In addition, serum MMP-9 was analysed in 37 paediatric TBE patients. Compared with control levels, both paediatric and adult TBE patients had significantly elevated serum MMP-9 levels. In most adult patients, serum MMP-9 levels peaked at hospital admission, with higher serum MMP-9 levels observed in patients with encephalitis than in patients with meningitis. Elevated serum MMP-9 levels were observed throughout hospitalisation but decreased to normal levels at follow-up. Serum MMP-9 levels correlated with clinical course, especially in patients heterozygous for the single-nucleotide polymorphism rs17576 (A/G; Gln279Arg) in the MMP9 gene. The results highlight the importance of MMP-9 in the pathogenesis of TBE and suggest that serum MMP-9 may serve as a promising bioindicator of TBE in both paediatric and adult TBE patients.
Keywords: dospělí; Tick-borne encephalitis; viry klíšťové encefalitidy; Cerebrospinal fluid; Humans; Matrix Metalloproteinase 9; klíšťová encefalitida; Encephalitis Viruses, Tick-Borne; Adult; Encephalitis, Tick-Borne; Matrix matalloproteinase; biologické markery; Neuroinfection; jednonukleotidový polymorfismus; lidé; Polymorphism, Single Nucleotide; dítě; Child; Biomarkers; matrixová metaloproteinasa 9